EMERGENCY NURSING ANALYSIS PREVENTION AND TREATMENT OF COGNITIVE DYFUNCTION AFTER TRAUMATIC BRAIN INJURY: LITERATURE REVIEW - Alivian, Galih Noor; Hidayat, Arif Imam; Awaludin, Sidik; Purnawan, Iwan (International Journal of Biomedical Nursing Review, 2022)
Introduction: Traumatic brain injury or traumatic brain injury according to the national consensus of treatment head trauma defines traumatic brain injury as mechanical trauma to the head either directly or indirectly that can cause disturbance neurological functions such as physical, cognitive and psychosocial disorders both temporarily nor permanent. This literature review aims to determine the prevention and treatment of cognitive dysfunction after traumatic brain injury. Literature search with using the ProQuest, PubMed, Garuda and Google Scholar databases with 2017-2022 publication range. Articles that meet the criteria are analyzed and rated quality according to inclusion and exclusion. Obtained ten articles discussing related to the prevention and treatment of cognitive dysfunction after traumatic brain injury, two articles using the literature review method. The results of the analysis of the 5 articles show below there are various alternatives can be used in the prevention and treatment of people with cognitive dysfunction or disorders positive after traumatic brain injury such as the use of trehalose drugs, computer-assisted cognitive stimulation or neurocognition, use of neurofeedback, prophylactic therapy, neuroradiographic imaging and basic and optional neurologic examinations use of anti-epileptic drugs (OATs). Until now there is no therapy that can be applied for primary brain injury, therapy for people with cognitive impairment focused on neurocognitive rehabilitation in cognitive impairment after traumatic brain injury